1981
DOI: 10.1523/jneurosci.01-09-00936.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serotonin on the generation of the motor program for swimming by the medicinal leech

Abstract: for advice on the bioassay for serotonin; and Janis Weeks for her helpful criticism of this manuscript. ' Present address and that to which all reprint requests should be ,' Terms such as "swim" and "swimming" will be used as shorthand sent: Department of Neurobiology, Harvard Medical School, 25 Shat-for longer phrases such as "motor program for swimming." SII will be tuck Street, Boston, MA 02115. used as an abbreviation for swim-initiating interneuron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
129
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(138 citation statements)
references
References 22 publications
8
129
0
1
Order By: Relevance
“…Neuromodulation may also play an important role in driving the networks, as has been shown in the crustacean stomatogastric ganglion (Nusbaum et al, 2001). In the leech, serotonin is known to promote swimming (Willard, 1981;Mangan et al, 1994) and dopamine has recently been shown to modulate crawling (Crisp and Mesce, 2004). Of primary interest is the mechanism by which the two CPGs generate oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromodulation may also play an important role in driving the networks, as has been shown in the crustacean stomatogastric ganglion (Nusbaum et al, 2001). In the leech, serotonin is known to promote swimming (Willard, 1981;Mangan et al, 1994) and dopamine has recently been shown to modulate crawling (Crisp and Mesce, 2004). Of primary interest is the mechanism by which the two CPGs generate oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin plays a role in exciting several invertebrate behaviors, for example, stimulating the flexed posture of the lobster (Livingston et al, 1980), swimming behavior in the leech (Willard, 1981), sensitizing the gill withdrawal reflex of Aplysia (Kandel and Schwartz, 1982;Siegelbaum et al, 1982), and intensifying the feeding behavior of several molluscs (Kupfermann and Weiss, 1981;Gelperin, 1981 Figure 11. Serotonin excitation of the buccal feeding network in Liman.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT is important for regulation of locomotion in some invertebrates (Willard 1981;Mackey and Carew 1983;Nusbaum 1986), and it has been previously suggested that both 5-HT and DA might contribute to the regulation of larval motor function in Drosophila (Mackey and Carew 1983;Neckameyer 1996;Cooper and Neckameyer 1999). We do not detect a significant increase in locomotion in larvae that express DVMAT in 5-HT neurons using TrH-Gal4 (Figure 2A, TrH), in DA neurons using TH-Gal4 (Figure 2A, TH), or, in a separate set of experiments, in both DA and 5-HT neurons using DdcGal4 ( Figure S4).…”
Section: Rescue Strategymentioning
confidence: 99%